2018
DOI: 10.3390/su10041080
|View full text |Cite
|
Sign up to set email alerts
|

Estimating the Efficiency and Impacts of Petroleum Product Pricing Reforms in China

Abstract: Abstract:The efficiency and effects analysis of a new pricing mechanism would have significant policy implications for the further design of a pricing mechanism in an emerging market. Unlike most of the existing literature, which focuses on the impacts to the macro-economy, this paper firstly uses an econometrics model to discuss the efficiency of the new pricing mechanism, and then establishes an augmented Phillips curve to estimate the impact of pricing reform on inflation in China. The results show that: (1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 40 publications
0
9
0
Order By: Relevance
“…Through bilateral and multilateral relations with these countries, China seeks to make vital raw materials available to sustain its own economy. At present, economic growth in China is facing development constraints to their energy supply [2]. Among the energy resources, the supply of petroleum is a major concern.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Through bilateral and multilateral relations with these countries, China seeks to make vital raw materials available to sustain its own economy. At present, economic growth in China is facing development constraints to their energy supply [2]. Among the energy resources, the supply of petroleum is a major concern.…”
Section: Introductionmentioning
confidence: 99%
“…China became the world's largest importer of petroleum in September 2013, surpassing the United States, as depicted in Figure 1. China also surpassed the United States in annual gross crude oil imports in 2017, importing 8.4 million barrels per day (b/d) compared with 7.9 million b/d for the United States [2]. At present, China is the world's largest importer of petroleum; therefore, the substantial petroleum demand has driven China to engage in trade relations with many countries and to import huge quantities from various sources.…”
Section: Introductionmentioning
confidence: 99%
“…Alternative to reacting to the market, Liu et al [18], Deng et al [19], Ma [20], Sukagawa [21], and Wårell [22] studied alternative solutions to reducing the erratic pricing trends of commodities. Liu et al [18] found using price reforms to artificially increase commodity pricing had disastrous impacts to the downstream organizations.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Liu et al [18] found using price reforms to artificially increase commodity pricing had disastrous impacts to the downstream organizations. Deng et al [19] studied the feasibility and related efficiency of a national commodity pricing mechanism, finding current methods of Chinese pricing to be inadequate, largely due to the long duration between adjustment periods. In response to these fluctuating pricing, many organizations have begun to rely on the concept of "spot iron ore pricing".…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation